EKSEKUSI BARANG BUKTI PADA PERKARA ILLEGAL LOGGING DI PENGADILAN NEGERI SEMARANG - Hani Irham Dessetya, Pujiyono ,Bambang Dwi Baskoro (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
One of the problems in the environmental field in the forestry sector is the problem of illegal logging or known by the term